Nilai-nilai Pendidikan Karakter dalam Kumpulan Cerpen Rumah Ibu Karya Harris Effendi Thahar - Sartika, Yulia; Gani, Erizal (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2023)
This study aims to describe the values of character education contained in the collection of short stories Rumah Ibu by Harris Effendi Thaha, to describe the values of character education that often appear in the collection of short stories Rumah Ibu by Harris Effendi Thahar, to describe the values of character education that rarely appears in the short story collection Rumah Ibu by Harris Effendi Thahar, and describes the values of character education that are not found in the short story collection Rumah Ibu by Harris Effendi Thahar. This type of research is qualitative research using descriptive method. The data in this study are narrative sentences and units of events that contain character education values. Sources of data in this study were 12 short stories contained in the collection of short stories Rumah Ibu by Harris Effendi Thahar. The results showed that there were 18 values of character education in the short story collection Rumah Ibu by Harris Effendi Thahar, the value of character education that often appears is the value of religious character education, the value of character education that rarely appears is the value of disciplined and democratic character education.